Household air pollution and lung function in Indian adults: a cross-sectional study - Dave, Mona; Ahankari, Anand S.; Myles, Puja R.; Arokiasamy, Perianayagam; Uttamacharya; Khobragade, Pranali; Mortimer, Kevin; Fogarty, Andrew W. (International Union Against Tuberculosis and Lung Disease, 2017)
Exposure to air pollution produced by cooking is common in developing countries, and represents a potentially avoidable cause of lung disease. Cross-sectional data were collected by the World Health Organization's Study on Global AGEing and Adult Health conducted in India between 2007 and 2010. Exposure to biomass cooking was also associated with a decrease in forced expiratory volume in 1 s (FEV1) (-70 ml, 95%CI -111 to -30) and FEV1/FVC (forced vital capacity) ratio (-0.025, 95%CI -0.035 to -0.015) compared to those who were not exposed. These associations were predominantly observed in males (P < 0.05 for interaction analyses). Intervention studies using non-biomass fuels in India are required to ascertain potential respiratory health benefits.